EVALUASI FAKTOR KEBUTUHAN LISTRIK UNTAD UNTUK MENGETAHUI PROPORSI LISTRIK YANG DIGUNAKAN DARI DAYA YANG TERSEDIA MELALUI AUDIT ENERGI - Mukhlis, Baso (MEKTEK, 2010)
Components that affect the amount of electricity payment is determined by the cost of kwh and therequested amount of power connected to the PLN. The amount of the charges is directly proportional tothe amount of load or wattage is connected while the power associated with the need factor. Factordemand shows the proportion of electricity used from the total available power. The ideal factor needsto be in the range of figures 60% - 80% .. If these values are low, then there is the possibility of a contractmade to PLN's power is too high that will affect the cost burden that must be paid. To serve theelectricity needs in the campus environment, the University of Tadulako mememiliki 29 meter connectedwith a power ranging from 450 VA sd 345 000 VA. Based on data from electricity bills in 2005, new Untadpay as much as Rp 573.544.300 per year or an average of Rp 47.795.358 per month, but based on datautility bills year 2008/2009 Untad has paid of Rp 956.114.955 per year or an average of Rp 79.676.246 permonth.The result showed that some of the resources that exist in the environment are connected Untad is below60% (not ideal), so it must be lowered to reduce electricity costs to be paid each month to the PLN.